Persepsi Masyarakat Sunda terhadap Pemanfaatan Beragam Tanaman Pekarangan di Desa Solear, Tangerang, Banten - Sri Hartati; Elizabeth Novi Kusumaningrum (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2026)
The rapid growth and development of urban communities in the central area of Tangerang Regency, followed by advances in information technology, have indirectly influenced changes in the lifestyles of rural communities in the regency. The purpose of this study was to identify and describe the use of plants growing in the yards of Sundanese communities in Solear Village, Solear District, Tangerang Regency, Banten. This study used a qualitative descriptive method conducted through a survey to collect data on yard plant species and interviews on their utilization by the Sundanese community in the village. The data was analyzed through reduction, grouping, data presentation, and conclusion drawing. Data analysis from yard surveys and interview results was carried out by classifying plant species and patterns of use based on their functions and the local wisdom of the community. The results of the study show that there are 55 species of plants growing in the yards of the Sundanese community in Solear Village, which are used in daily life for six types of benefits, namely as vegetables, kitchen spices, fruits, traditional medicine, ornamental plants, and building materials. This research contributes to ethnobotanical studies by providing systematic data on the use of yard plants, which supports the preservation of traditional knowledge and sustainable management of biological resources in areas affected by urbanization.